APPLICATION OF BIOPOLYMER FILMS FOR SUSTAINABILITY OF EDIBLE OILS - Popović, Senka (Journal on Processing and Energy in Agriculture, 2021)
Lipid oxidation is a major cause of off-flavors and loss of nutrients in fat-containing foods and oils. The prevention or retardation of those deteriorative reactions of oil during processing and storage is required.  Commercially available synthetic packaging materials are causing serious environmental problems due to their non-degradability. To reduce environmental impacts associated with synthetic plastics, biopolymer materials have a great potential to be used instead. Further, biopolymers play an important role in food preservation because of their antioxidant and antimicrobial activities. Packing system comprise of natural active materials can improve shelf life of oil packed, minimize oxidation and improve mechanical, barrier and biological properties of biopolymer films. In this paper, to determine effect of usage biopolymer materials for oil packing, different  edible oils and biopolymer materials were observed.
Keywords: edible oil, oil oxidation, active packaging, biopolymer films